Objektifikasi Qiá¹¢Äs Dan Diyat: Sebuah Tawaran Pembaharuan KUHP - Sulaiman, Akhmad; Ikhlas, Nur (IAIN Surakarta, 2018)
The reporting media indicates that the killing ceses in Indonesia keep on rise. It means that applying killing criminal law that refers to KUHP is not effective. This condition requires KUHP reforming because the right of human life must be vouched by the government. The criminal law of Indonesia must punish a killer more forceful. The writers offer qiá¹£Äs and diyat to be applied in Indonesia but they have to pass through objectification. According to Kuntowijoyo, objectification is interpreting religionâ€™s internal doctrines into objective categories in order to be able to be applied, actualized,Â and accepted by moslem and nonmoslem. It is research and development that strives for developing Kuntowijoyoâ€™s objectification on KUHP reforming. With changing Â qiá¹£Äs term into die punishment, diyat into compensation for victimâ€™s family, and adjusting with objective condition in Indonesia, qiá¹£Äs and diyat will be accepted by every national of Indonesia and become solution of criminal law of Indonesia that is not effective.